«Εις τα χείλη της αβύσσου όπου με έφερε η βραδύτης των εν τέλει»: Τα οικονομικά των ελληνικών εφημερίδων της Θεσσαλονίκης και ο Μακεδονικός Αγώνας - Νίγδελης Παντελής Μ. (Μακεδονικά, 2011)
The question of financial backing for the Greek newspapers published inThessaloniki in the Ottoman years is a subject about which very little isknown. Documents and letters in the archives of the «Association for the Dissemination of Greek Letters» and of Stephanos Dragoumis (Gennadios Library), published here for the first time, shed light on certain aspects of thismatter. Shortly before as well as during the armed phase of the MacedonianStruggle, the owners of the newspapers Pharos tis Thessalonikis and Aletheia,which were plagued by chronic financial problems, saw in this important development an opportunity to turn their journals into state-supported enterprises. To this end the former canvassed patriotic circles in Athens to try tofind an association or group of associations willing to take over the Pharos tisThessalonikis, while his colleague sought to persuade the Foreign Ministry toincrease its annual subsidy to Aletheia to approximately the amount of the initial investment, with the aim of making it a daily propaganda instrument, especially since the rival Pharos tis Thessalonikis had in the meantime ceasedpublication. In the end both proposals failed, defeated by the indifference ornegativity of the national centre.